2013
DOI: 10.1021/mp300432s
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Conjugating Polyethylenimine with Chondroitin Sulfate to Promote CD44-Mediated Endocytosis for Gene Delivery

Abstract: Polyethylenimine (PEI) is one of the most potent synthetic gene delivery vectors because of its high transfection efficiency. Although PEI has been used as a delivery vehicle for a long while, its toxicity is always an issue for clinical applications. In this study, we introduced a low molecular weight PEI of 10 kilodaltons to chondroitin sulfate (CS) via a Michael addition method. By adjusting weight ratios between cationic PEI and anionic CS, the intermolecular or intramolecular, or both, electrostatic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 47 publications
3
42
0
4
Order By: Relevance
“…5B). Lo et al 47) reported that pDNA/CS-modified PEI was primarily taken up by U87 cells based on clathrinmediated endocytosis. These results suggest that CS-coated particles were predominantly taken up by clathrin-mediated endocytosis.…”
Section: Fig 7 In Vivo Gene Expression Of Each Complex Administeredmentioning
confidence: 99%
“…5B). Lo et al 47) reported that pDNA/CS-modified PEI was primarily taken up by U87 cells based on clathrinmediated endocytosis. These results suggest that CS-coated particles were predominantly taken up by clathrin-mediated endocytosis.…”
Section: Fig 7 In Vivo Gene Expression Of Each Complex Administeredmentioning
confidence: 99%
“…2). Так как ХС -это моле-кулы с высокой молекулярной мас-сой (>10 кДа), они оказывают эф-фект посредством взаимодействия с белками-рецепторами CD44, TLR4 и ICAM1 [14] на поверхности хондро-цитов. Связываясь с рецептором CD44, ХС снижают транскрипцию провоспалительного сиг-нального фактора NF-кВ, блокируя провоспалительные сигнальные пути с участием белков ADAMTS, ММР, ИЛ1β и др.…”
Section: молекулярные эффекты хондрогарда при остеоартрите и грыжах мunclassified
“…Chondroitin sulfate has been widely used in drug delivery as a hydrophilic component of self-assembled nanocarriers (33)(34)(35)(36)(37)(38)(39). In addition, due to the anionic charge and the ability to bind to CD44, chondroitin sulfate has been used in combination with polymeric gene carriers to reduce the cationic charge (40)(41)(42)(43)(44)(45)(46) and improve the target specificity (45)(46)(47). The chondroitin sulfate associated with cationic gene carriers is also shown to modify intracellular trafficking of the gene complex (promote endosomal escape and accumulation at the nuclear periphery) in favor of gene transfection (48).…”
Section: Chondroitin Sulfatementioning
confidence: 99%